Are Neglected Plants the Food for the Future?. (3rd March 2016) - Baldermann, S.; Blagojević, L.; Frede, K.; Klopsch, R.; Neugart, S.; Neumann, A.; Ngwene, B.; Norkeweit, J.; Schröter, D.; Schröter, A.; Schweigert, F. J.; Wiesner, M.; et al.
ABSTRACT: Malnutrition, poor health, hunger, and even starvation are still the world's greatest challenges. Malnutrition is defined as deficiency of nutrition due to not ingesting the proper amounts of nutrients by simply not eating enough food and/or by consuming nutrient-poor food in respect to the daily nutritional requirements. Moreover, malnutrition and disease are closely associated and incidences of such diet-related diseases increase particularly in low- and middle-income states. While foods of animal origin are often unaffordable to low-income families, various neglected crops can offer an alternative source of micronutrients, vitamins, as well as health-promoting secondary plant metabolites. Therefore, agricultural and horticultural research should develop strategies not only to produce more food, but also to improve access to more nutritious food. In this context, one promising approach is to promote biodiversity in the dietary pattern of low-income people by getting access to nutritional as well as affordable food and providing recommendations for food selection and preparation. Worldwide, a multitude of various plant species are assigned to be consumed as grains, vegetables, and fruits, but only a limited number of these species are used as commercial cash crops. Consequently, numerous neglected and underutilized species offer the potential to diversify not only the human diet, but also increase food production levels, and, thus, enable more sustainable and resilient agro- and horti-food systems. To exploit the potential of neglected plant (NP) species, coordinated approaches on the local, regional, and international level have to be integrated that consequently demand the involvement of numerous multi-stakeholders. Thus, the objective of the present review is to evaluate whether NP species are important as "Future Food" for improving the nutritional status of humans as well as increasing resilience of agro- and horti-food systems.